The Influence of Management Information System to Management Control System - Sihar Tambun; Vienda A. Kuntjoro (International Conference On Law, Business and Governance (ICon-LBG), 2013)
Purpose – The purpose of this paper to recognize the most important indicators of managementinformation system that can influence the management control system.Design/methodology/approach – this study uses meta-analysis as the explanation approach as findingout the indicators of management information system that can influence the management control systemmay necessary be approved by empirical study for the next future research.Finding – The indicators of management information system supporting the quality of managementbefore the management control system can be fully implemented.Originality/value – The characteristic of each indicator of management information system brings theinformation that shows the result from that information so that by studying this information at eachdifferent kind of situation will affect not only management quality but also the different strategy ofmanagement to applied control system based on the knowledge management level.